Dinamika Pendidikan Islam di Kabupaten OKU: Studi Sejarah pada Abad ke-20 hingga Kini - Azwar Aripin; Faozan (PT. Panca Publishing Indonesia, 2026)
Islamic education plays an important role in the social, cultural, and religious development of Indonesian society. This study aims to analyze the dynamics of Islamic education in Ogan Komering Ulu (OKU Regency) from the twentieth century to the present, focusing on the development of Islamic educational institutions, the transformation of pesantren and madrasah, and their adaptation to social changes and national education policies. This research employs a historical method with a qualitative approach through literature studies, document analysis, and examination of historical sources related to local Islamic education development. The findings reveal that Islamic education in OKU developed from community-based learning systems in mosques, surau, and religious gatherings into more structured institutions such as pesantren and madrasah. Pesantren functioned as institutions for preserving Islamic scholarly traditions and character formation, while madrasah represented the modernization of Islamic education through the integration of religious and general sciences. This study confirms that Islamic education in OKU demonstrates strong adaptability in maintaining Islamic identity while responding to contemporary educational challenges.